2021
DOI: 10.1038/s41562-020-01036-x
|View full text |Cite
|
Sign up to set email alerts
|

An implicit memory of errors limits human sensorimotor adaptation

Abstract: After extended practice, motor adaptation reaches a limit in which learning appears to stop, despite the fact that residual errors persist. What prevents the brain from eliminating the residual errors? Here we found that the adaptation limit was causally dependent on the second order statistics of the perturbation; when variance was high, learning was impaired and large residual errors persisted. However, when learning relied solely on explicit strategy, both the adaptation limit and its dependence on perturba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
138
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(176 citation statements)
references
References 90 publications
16
138
5
Order By: Relevance
“…Notwithstanding these studies, we found that on average participants' learning plateaued before eliminating error, with asymptotic learning levels statistically different from the degree of imposed rotation for all rotational groups (30°, 45°, 60°), regardless of the amount of preparation time enforced. These findings are consistent with previous reports which have suggested that sustained errors during visuomotor adaptation are a product of the implicit learning system; either suppressing alternative learning mechanisms which may be able to overcome persisting errors (Shmuelof et al, 2012;Vaswani et al, 2015) and/or modulating the system's sensitivity to errors dependent on their size, variability and history (Albert et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notwithstanding these studies, we found that on average participants' learning plateaued before eliminating error, with asymptotic learning levels statistically different from the degree of imposed rotation for all rotational groups (30°, 45°, 60°), regardless of the amount of preparation time enforced. These findings are consistent with previous reports which have suggested that sustained errors during visuomotor adaptation are a product of the implicit learning system; either suppressing alternative learning mechanisms which may be able to overcome persisting errors (Shmuelof et al, 2012;Vaswani et al, 2015) and/or modulating the system's sensitivity to errors dependent on their size, variability and history (Albert et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…We found that motor adaptation was impaired in the 45° and 60° rotational groups, when planning time was restricted to 0.35 seconds. This result is in line with previous studies who report reduced error compensation when preparation times are limited (Fernandez-Ruiz et al, 2011;Leow, Gunn, et al, 2017;Leow, Marinovic, Riek, & Carroll, 2017;Albert et al, 2021) and may reflect the suppression of explicit re-aiming/cognitive strategies. Additionally, impaired adaptation associated with restricted preparation times was coupled with an increased retention during no-feedback trials, which is consistent with the idea that learning involved more implicit, procedural processes (Fernandez-Ruiz et al, 2011;Haith et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Recent work suggests that error sensitivity in sensorimotor adaptation is likely not constant, but rather can vary depending on prior experience (Albert et al, 2021;Herzfeld et al, 2014;Marko et al, 2012;Wei & Körding, 2009). We modelled movement angle across each session with the state-space equations proposed by Smith et al (2006), and focused on changes in the retention and error sensitivity parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 15, 2021. ; https://doi.org/10.1101/2021.06.14.448375 doi: bioRxiv preprint perturbation schedules used during initial training was that the slow process accounted for a significant portion of the error reduction. Albert et al (2021) recently investigated the persistence of residual errors during motor adaptation in the context of implicit and explicit learning systems. Of importance to the present study, they propose that it is the implicit learning system which maintains a history for prior errors.…”
Section: Discussionmentioning
confidence: 99%
“…As we did not employ the experimental design that explicitly quantified these components, this is still an open question. Notably, however, a very recent study (Albert et al, 2021) demonstrated that the learning rate for the "implicit" motor learning process is sensitive to environmental statistics (e.g., perturbation consistency), suggesting that the "implicit" motor learning process is likely modulated by environmental uncertainty/surprise.…”
Section: Uncertainty and Motor Learningmentioning
confidence: 99%